Systematic Literature Study: Challenges and Opportunities for the Application of Withholding Tax in the Era of Globalization - Agusman Sianturi; Umi Kalsum; Luk Luk Fuadah; Rizka Novelia; Amri Utama (Green Publisher Indonesia, 2025)
The implementation of Withholding Tax (WHT) in Indonesia confronts multifaceted challenges encompassing both internal taxpayer factors—including staff understanding, motivation, and capacity—and external factors such as transaction complexity, administrative procedures, and limited system digitalization. Risks of incorrect withholding, tax avoidance, and sectoral compliance variations underscore the necessity for integrated strategic interventions. This study aims to analyze WHT challenges, identify opportunities, and examine strategies based on Tax Compliance Theory, considering taxpayers' attitude, subjective norms, and perceived behavioral control. The research employs a systematic literature review methodology, analyzing 50 peer-reviewed journals (Q1-Q3 international and S2-S3 national publications) published within the last decade. Literature selection followed rigorous inclusion criteria: studies specifically addressing WHT implementation, containing challenge and opportunity analyses, and demonstrating methodological rigor. The analytical framework utilized thematic synthesis to identify patterns across internal and external compliance factors, subsequently evaluated through the Tax Compliance Theory lens. Findings indicate that effective strategies include system digitalization, staff training, taxpayer education, incentive-penalty mechanisms, regulatory harmonization, and real-time monitoring and auditing. Notably, this study contributes novel insights by synthesizing WHT compliance challenges within the globalization context, particularly addressing cross-border digital transactions and fintech sector implications previously underexplored in Indonesian taxation literature. The integrated strategic framework proposed bridges theoretical understanding with practical implementation, offering evidence-based policy recommendations. Implementing these integrated strategies is expected to enhance voluntary compliance, minimize withholding errors, and strengthen WHT effectiveness across all sectors, including MSMEs and fintech.